Developing a character assessment instrument based on the school culture - Hidayah, Murti Ambarwati; Setiawati, Farida Agus (Graduate School of Universitas Negeri Yogyakarta & Himpunan Evaluasi Pendidikan Indonesia (HEPI), 2022)
This study aims to develop an instrument that is valid and reliable to measure the character of junior high school students. The developed instrument is a character assessment based on the school culture, used to facilitate teachers and schools in assessing student characters. This study is development research. The trial subjects involved in this study were 128 grade VIII students of state junior high schools in Bantul. The developed instrument was validated for the content by experts. The construct validity was analyzed using the confirmatory factor analysis (CFA), and the reliability was estimated using the omega reliability formula by McDonald. The result of the study is a character assessment instrument comprising six aspects with 12 indicators and 22 statements. The developed instrument has fulfilled the validity and reliability requirements. The content validity acquired an Aiken index of 0.87, while the CFA test acquired a loading factor score of each item being valid with Î» > 0.5 and t-value >1.96. The student character measurement fits the theorized model (Ï‡2 = 230.719; (p) = 0.08; RMSEA = 0.040; and CFI = 0.964) and McDonald's composite reliability estimation result 0.907. The score of students' characters in the developing category were 63.3%, 18.8% for the early development category, 11.7% for the requiring assistance category, and 6.3% for the cultured category